INFLUENCE OF COMBINED APPLICATIONS OF SIAM WEED COMPOST AND INORGANIC FERTILISER ON TOMATO PERFORMANCE - Akinrinola, Tajudeen Bamidele; Tijani-Eniola, Hassan (Journal of Agricultural Sciences (Belgrade), 2022)
Abstract: Tomato is an important vegetable crop with high soil nutritional requirements. Hence, improvement in soil fertility status must be met through the use of readily availability nutrient sources. Chromolaena odorata (CC) is wide spread in the country and its compost has the potential of improving tomato yield. However, there is dearth information on response of tomato to CC and NPK fertiliser combination. This experiment evaluates CC at 0, 6, 8 and 10 t/ha; and NPK 15-15-15 at 0, 15 and 30 kg N/ha. It was laid out in completely randomized design and randomized block design for pot and field studies respectively. In the pot and field experiments, increasing level of fertiliser application increased plant height, while the inverse was observed with respect to days to 50% flowering, with no significant difference observed between treatments. Combined application of 8 t/ha CC plus 30 kg N/ha NPK 15-15-15 fertiliser gave significantly higher number of leaves, number of branches, leaf area and highest fruit set at 49 DAT compared to other treatments. On the field, number of fruit/plant (20.89) was significantly higher with combined application of 10 t/ha CC plus 30 kg N/ha NPK 15-15-15 fertiliser, while 8 t/ha CC plus 30 kg N/ha NPK 15-15-15 fertiliser treatment gave significantly higher fruit size (64.61 g) and yield (31.73 t/ha) compared to the control (11.33, 32.09 g and 9.66 t/ha, respectively). The application of 8 t/ha CC plus 30 kg N/ha NPK 15-15-15 fertiliser was therefore recommended.   Сажетак: Парадајз је важна биљна култура са високим захтевима за исхрану земљишта. Према томе, побољшање стања плодности тла мора бити испуњено кроз коришћење доступних извора хранљивих материја. Цхромолаена одората (ЦЦ) је широко распрострањена у земљи и њен компост има потенцијал да побољша принос парадајза. Међутим, недостају информације о одговору комбинације парадајза и ЦЦ и НПК гнојива. Овај експеримент процењује ЦЦ на 0, 6, 8 и 10 т / ха; и НПК 15-15-15 на 0, 15 и 30 кг Н / ха. Израђен је у потпуно рандомизираном дизајну и рандомизираном блок дизајну за лонац и теренске студије. У покусима у лонцу и на пољу, повећање нивоа примене ђубрива повећало је висину биљке, док је инверзно посматрано у односу на дане до 50% цветања, без значајне разлике између третмана. Комбинована примена 8 т / ха ЦЦ плус 30 кг Н / ха НПК 15-15-15 ђубрива дала је значајно већи број листова, број грана, површина листа и највиши сет воћа на 49 ДАТ у поређењу са другим третманима. На терену је број воћа / биљака (20,89) био значајно већи са комбинованом применом 10 т / ха ЦЦ плус 30 кг Н / ха НПК 15-15-15 ђубрива, док је 8 т / ха ЦЦ плус 30 кг Н / ха Третман НПК 15-15-15 омогућио је значајно већу величину воћа (64,61 г) и принос (31,73 т / ха) у односу на контролу (11,33, 32,09 г и 9,66 т / ха, респективно). Стога се препоручује примена 8 т / ха ЦЦ плус 30 кг НК / 15-15-15 ђубрива НПК.
Keywords: NPK 15-15-15 fertiliser; Combined fertiliser application; Tomato growth and yield; Chromolaena odorata compost